MODEL PENJAMINAN MUTU PEMBELAJARAN AL-QUR’AN DI MI PLUS ASY SYUKRIYYAH TANGERANG - Sudirman; Khoirul Anwar; Olivia Fachrunnisa (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to describe the quality assurance model of Al-Qur’an learning at MI Plus Asy Syukriyyah Tangerang. Despite the growing implementation of quality assurance systems in Islamic education, studies specifically examining an integrated quality assurance model for Al-Qur'an learning that combines differentiated learning, academic supervision, continuous evaluation, and Qur'anic culture remain limited. This study addresses this gap by proposing an integrated quality assurance model for Al-Qur'an learning in Islamic elementary education. The study employed a descriptive qualitative approach using interviews, observations, and documentation studies as data collection techniques. The research informants consisted of the principal, vice principal of curriculum, Al-Qur’an coordinator, tahsin and tahfidz teachers, and students’ parents. The findings reveal that the quality assurance system of Al-Qur’an learning was developed integratively through strengthening input standards, learning processes, monitoring and evaluation, and Qur’anic culture. The learning process was implemented using the Utsmani method through halaqah grouping based on students’ abilities, differentiated learning, periodic supervision, and tiered evaluations through UKM and munaqasyah. Supporting factors include leadership commitment, teacher competence, parental involvement, and a Qur’anic school culture. Meanwhile, inhibiting factors include differences in students’ abilities, limited learning time, and the less optimal implementation of muroja'ah at home. The novelty of this study lies in the integration of quality planning, differentiated halaqah-based learning, tiered evaluation, academic supervision, and Qur'anic culture into a single quality assurance framework. The findings contribute theoretically to the development of quality assurance studies in Islamic education and practically provide a reference model for Islamic schools seeking to strengthen the quality of Al-Qur'an learning programs.